Therapy for Thrombotic Thrombocytopenia Purpura: Past, Present, and Future - Chapman, Kent; Yuen, Sam (Seminars in Thrombosis and Hemostasis, 2014)
While clinical recognition of thrombotic thrombocytopenia purpura (TTP) has been evident for almost 90 years, the pathological basis of this disorder has only, relatively, recently been elucidated. Consequently, options for treating TTP had evolved rather slowly for many years. Despite this, current treatment practices of intensive plasma exchange often with immune modulation have seen survival rates increase dramatically. Nevertheless, the current understanding of TTP may witness the cusp of a new era for this disorder, with new and emerging treatments nearing clinical practice that specifically target the root cause of TTP. Some of these targeted approaches may even see the beginning of plasma-free treatments for TTP, with potentially faster recoveries and fewer long-term adverse effects.
Keywords: thrombotic thrombocytopenia purpura; TTP; therapy; von Willebrand cleaving protease; ADAMTS-13